The effect of a complex of active metabolites of vitamin D3 with vikasol on the periodontal state of rats - Skiba, A. V.; Savelyeva, N. N.; Schnеider S. A.; Tkachenko, E. K. (Journal of Education, Health and Sport, 2018)
Purpose of the study. The study of the periodontoprotective properties of the complex of a mixture of active metabolites of cholecalciferol - 1,25 (OH)2D3 and 24,25(OH)2D3 with a synthetic analogue of vitamin K - vikasol in experimental periodontitis in rats. Materials and methods The study was carried out on 18 white male rats for 1.5 months. age, divided into 3 groups. Group 1 (4 individuals) comprised intact rats. In the rats of the 2nd and 3rd groups (7 individuals each), the parodontitis model was reproduced by oral administration of a 10% solution of pelentane, and also by replacing drinking water with a 2% solution of EDTA ad libitum. In group 3, rats were injected daily with a mixture of hormonal forms of vitamin D3 (1,25 (OH)2D3 and 24,25(OH)2D3) against a background of combined effects of pelentane and EDTA. The duration of the experiment was 60 days. Results and conclusions. It is established that the complex of a mixture of two hormonal-active forms of cholecalciferol with vikasol has significant periodontoprotective properties. The obtained data substantiate the inclusion of vitamin D3 in the composition of perioodontoprotective agents in the treatment of periodontitis.